Feeding and feedback in the nucleus of NGC 613. Issue Volume 15:Issue S359(2020) (March 2019) - da Silva, Patrícia; Steiner, J. E.; Menezes, R. B.
Abstract: Active Galactic Nuclei (AGN) are objects in which a supermassive black hole is fed by gas and, as this generates energy, can ionise the environment and interact with it by jets and winds. This work is focused on the processes of feeding and feedback in the nucleus of NGC 613. This object is a case in which both phenomena can be studied in some detail. The kinematics and morphology of the molecular gas trace the feeding process while the ionization cone, seen in [O iii]λ5007 and soft X-rays, as well as the radio jet and wind/outflows are associated with feedback processes. In addition, we see 10 HII regions, associated with nuclear and circumnuclear young stellar populations, dominant in the optical, that makes the analysis complicated, though more interesting. For all these phenomena, NGC 613 nucleus is a vibrant example of the interplay between the AGN and the host galaxy.